Assessment of Dual Carriageway for Sustainable Socio-Economic Development in Ado Ekiti, Nigeria - A.S, Ale (International Journal of Sustainable Development & World Policy, 2019)
Various studies have been carried out on urban dual-carriage ways and its implication on sustainable development in different parts of world. In Nigeria, work on dual carriageway for sustainable development still remained under explored. This study therefore, focused on urban dual carriageway for sustainable development of Ado- Ekiti and to enhance good quality of life of the people. Data for this study were obtained from primary and secondary sources as well as field observation.250 copies of questionnaire were administered in 5 purposively selected areas in Ado-Ekiti with the use of questionnaire. Simple random sampling method was used to choose 30 houses at an interval of 10 houses through balloting .Secondary data were sourced through journal articles and edited books. Data were analyzed using both descriptive and inferential statistic techniques. Chi-square statistical method were adopted to test the two hypotheses stated (i) effect of dual carriageway on socio-economic activities in the area and (ii) the impact of dual carriageway on travel time and cost of transport in the area at 5% level of significance. It was discovered that dual carriageway has great influence on socio - economic activities, trip generation, travel time, cost of transport among others in Ado- Ekiti